SELF EFFICACY AKSEPTOR KB TERHADAP ALAT KONTRASEPSI DENGAN PEMILIHAN KB MKJP DAN NON MKJP - Aris Noviani; Yeni Anggraini (Stikes Muhammadiyah Klaten, 2023)
The low utilization of KB MKJP (Long Term Contraceptive Method) is one of the main problems in the Family Planning program. Acceptors' wrong assumptions about KB MKJP can result in incompatibility of acceptors in using contraception. Self-efficacy is also an internal factor that influences the views or perceptions of an acceptor in choosing the type of family planning. This study used a cross-sectional design using the Yate's Correction test. This study aims to analyze the relationship between the self-efficacy of contraceptive use and the selection of KB MKJP and Non-MKJP. The sampling technique used was purposive sampling. The sample in this study were couples of childbearing age (PUS) aged 15-49 years who used contraception, totaling 35 respondents. The results showed that there was a significant relationship between the self-efficacy of family planning acceptors on the selection of MKJP and Non-MKJP KB, with a p-value <0.05. The participation of all levels of society needs to be increased to reduce dropout rates and increase the use of long-term contraceptives.